Communications and networking : an introduction - Cowley, John (London : Springer, 2012)
This clear and easy to follow textbook, presents a detailed introduction to the essentials of networking and communications technologies, supported by numerous diagrams, examples and exercise designed to improve confidence in using and understanding communications systems.
Includes index.
nmn 24/10/2017
Loans
Keywords: Computer networks; Computer networks--Security measures; Computer network architectures; Computer science